2009
DOI: 10.3109/10715760903247264
|View full text |Cite
|
Sign up to set email alerts
|

Lignin-derived lignophenols attenuate oxidative and inflammatory damage to the kidney in streptozotocin-induced diabetic rats

Abstract: This study investigated the effects of lignin-derived lignophenols (LPs) on the oxidative stress and infiltration of macrophages in the kidney of streptozotocin (STZ)-induced diabetic rats. The diabetic rats were divided into four groups with 0%, 0.11%, 0.33% and 1.0% LP diets. The vehicle-injected controls were given a commercial diet. At 5 weeks, superoxide (O(2)(-)) production, macrophage kinetics, the degree of fibrosis in glomeruli and mRNA expression for monocyte chemoattractant protein-1 (MCP-1) were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The decrease of oxidative and inflammatory damage to the kidney in streptozotocin-induced diabetic rats due to lignin-derived lignophenols was reported by Sato et al [51]. Similar to these results, low molecular weight lignins were tested regarding their potential as anti-emphysema agents in vitro [52].…”
Section: Lignin Antimicrobial Activitysupporting
confidence: 57%
“…The decrease of oxidative and inflammatory damage to the kidney in streptozotocin-induced diabetic rats due to lignin-derived lignophenols was reported by Sato et al [51]. Similar to these results, low molecular weight lignins were tested regarding their potential as anti-emphysema agents in vitro [52].…”
Section: Lignin Antimicrobial Activitysupporting
confidence: 57%
“…Lignin nanoparticles incorporated in polylactic acid (PLA) revealed an innovative capacity to inhibit the bacterial growth along the time [ 49 ]. The decrease of oxidative and inflammatory damage to the kidney in streptozotocin-induced diabetic rats due to lignin-derived lignophenols was reported by Sato et al [ 51 ]. Similar to these results, low molecular weight lignins were tested regarding their potential as anti-emphysema agents in vitro [ 52 ].…”
Section: Lignin Antioxidant Capacity and Bioactivitymentioning
confidence: 68%
“…In terms of diabetes control, it's reported that LPs from beech tree (Fagus crenata Blume) played an active role in attenuating oxidative stress and inflammatory damage, activating macrophages as well as promoting glomerular expansion in the kidneys of streptozotocin (STZ)-induced diabetic rats (Sato et al, 2009). LPs-containing diets were proved to be very helpful for lowering plasma triglyceride levels in rats fed a high-fat diet by potentially suppressing the expression of sterol regulatory element-binding protein (SREBP) and acetyl-CoA carboxylase (ACC) (Sato et al, 2012).…”
Section: Lignin-based Polymers/lignophenolsmentioning
confidence: 99%